Factors Related to Complaints of Lung Function Disorders In UPN Veteran Jakarta Employees - Prasetyo Risky Alamsyah; Fajaria Nurcandra; Cahya Arbitera; Fathinah Ranggauni Hardy (Respiratory Science, 2022)
Background: One characteristic of lung dysfunction is obstruction of airflow in the respiratory tract. The prevalence of COPD as lung function disorder among men in Indonesia is 3.7% and 2.7% in DKI Jakarta. One of the causes of decreased lung function is smoking. A large portion of UPN Veteran Jakarta employees is smoker. This research was aimed to determine risk factors of lung dysfunction among employees in UPN Veteran Jakarta. Method: A cross sectional study was conducted from April to May 2019 in UPN Veteran Jakarta. Total 102 samples of employees who work at UPN includes staff, lecturers, cooperative officers, office boys, and security guards were selected using purposive sampling. Measuring instruments used in this study were questionnaires, scales, microtoise and spirometer. Spirometer was used to measure lung function. Questionnaires to obtain data on gender, age, body mass index (BMI), employment status, education, allergies, history of lung disease, family history, Brinkman index, physical activity, vehicle emissions exposure and smoking environment. The data was analysed using the chi square test and logistic regression test Results: The results of the logistic regression test showed risk factors of lung dysfunction were BMI (POR: 4.718; 95% CI 1.673-13.305), history of lung disease (POR: 3,424; 95% CI 0.836-14.028) and smoking environment (POR: 2.956; 95% CI 0.953-9.168). Conclusion: The most influencing factors for lung dysfunction were BMI, history of lung disease, and smoking environment.